Cortical plasticity as a new endpoint measurement for chronic pain - Zhuo Min (SAGE Publishing, 2011)
Abstract Animal models of chronic pain are widely used to investigate basic mechanisms of chronic pain and to evaluate potential novel drugs for treating chronic pain. Among the different criteria used to measure chronic pain, behavioral responses are commonly used as the end point measurements. However, not all chronic pain conditions can be easily measured by behavioral responses such as the headache, phantom pain and pain related to spinal cord injury. Here I propose that cortical indexes, that indicate neuronal plastic changes in pain-related cortical areas, can be used as endpoint measurements for chronic pain. Such cortical indexes are not only useful for those chronic pain conditions where a suitable animal model is lacking, but also serve as additional screening methods for potential drugs to treat chronic pain in humans. These cortical indexes are activity-dependent immediate early genes, electrophysiological identified plastic changes and biochemical assays of signaling proteins. It can be used to evaluate novel analgesic compounds that may act at peripheral or spinal sites. I hope that these new cortical endpoint measurements will facilitate our search for new, and more effective, pain medicines, and help to reduce false lead drug targets.